2018
DOI: 10.24187/ecostat.2017.497d.1931
|View full text |Cite
|
Sign up to set email alerts
|

Standards of living and segregation in twelve French metropolises

Abstract: The socio-demographic contrasts between the 13 new metropolitan regions are relatively small compared to those observed in other European countries. At the national level, territorial disruption occurs more within regions than between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Our study, based on repeated general population seroprevalence measures, showed that while the overexposure to Covid-19 infection of first-generation immigrants was strongly linked to their living conditions at the beginning of the epidemic, the overexposure observed six months later for the first and especially the second generation, who have more social contacts more than their elders, is not the result of a lesser respect for barrier gestures or of more frequent outings than the native-born ( S1 Table ). It could result from micro-social structural effects, because of the phenomena of socio-spatial segregation [ 23 ] and territorialized socialization [ 24 ]. Second-generation immigrants are very often grouped together, facilitating the circulation of the virus in social groups where the prevalence is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, based on repeated general population seroprevalence measures, showed that while the overexposure to Covid-19 infection of first-generation immigrants was strongly linked to their living conditions at the beginning of the epidemic, the overexposure observed six months later for the first and especially the second generation, who have more social contacts more than their elders, is not the result of a lesser respect for barrier gestures or of more frequent outings than the native-born ( S1 Table ). It could result from micro-social structural effects, because of the phenomena of socio-spatial segregation [ 23 ] and territorialized socialization [ 24 ]. Second-generation immigrants are very often grouped together, facilitating the circulation of the virus in social groups where the prevalence is higher.…”
Section: Discussionmentioning
confidence: 99%
“…(20) Our study, based on repeated general population seroprevalence measures, showed that while the overexposure to Covid-19 infection of first-generation immigrants was strongly linked to their living conditions at the beginning of the epidemic, the overexposure observed six months later for the first and especially the second generation, who have more social contacts more than their elders, is not the result of a lesser respect for barrier gestures or of more frequent outings than the native-born (supplementary table 1). It could result from microsocial structural effects, because of the phenomena of socio-spatial segregation (21) and territorialized socialization. (22) Second-generation immigrants are very often grouped together, facilitating the circulation of the virus in social groups where the prevalence is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns have also been observed outside the United States. Floch (2017) finds higher levels of segregation for the highest income group across 12 French cities. One possible explanation for such patterns is that poorer residents might end up in more diverse neighborhoods than the richest residents.…”
Section: Comparing Segregation Across Countries and Citiesmentioning
confidence: 99%